A Review of Clinical Applications and Side Effects of Methotrexate in Ophthalmology - Ge Wang; Xiaoyan Peng (Journal of Ophthalmology)
Methotrexate (MTX) is a folate analog widely used against a range of diseases including malignancies and autoimmune disorders. Its high effectiveness-price ratio also won extensive application in ophthalmology. On the other hand, although MTX has an excellent pharmacological efficacy, MTX associated side effects in clinical use, which vary from patient to patient, are nonnegligible. There is no comparatively systematic review on MTX associated side effects and its risk factors. This review aimed to reveal novel clinical approaches of MTX and its adverse effects in order to provide a reference for ophthalmic scholars in clinical application of MTX.